2021
DOI: 10.3390/ijms22147267
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Role of Lipids in the Molecular Mechanism of Membrane Proteins

Abstract: Membrane proteins have evolved to work optimally within the complex environment of the biological membrane. Consequently, interactions with surrounding lipids are part of their molecular mechanism. Yet, the identification of lipid–protein interactions and the assessment of their molecular role is an experimental challenge. Recently, biophysical approaches have emerged that are compatible with the study of membrane proteins in an environment closer to the biological membrane. These novel approaches revealed spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 153 publications
(183 reference statements)
0
10
0
Order By: Relevance
“…As we are confident of our activity assay, we sought out a less trivial explanation of this discrepancy. In view of the growing body of evidence for the importance of lipids in the mechanisms of membrane proteins, including allostery [ 34 ], we measured the substrate saturation profile for DDM-solubilized Dh-mPPase and compared it with the profile for the IMV-bound enzyme (the uppermost curves in Figure 3 and Figure 5 ). This comparison demonstrated the close similarity of the two profiles ( Figure S3 ) and the parameters derived therefrom ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…As we are confident of our activity assay, we sought out a less trivial explanation of this discrepancy. In view of the growing body of evidence for the importance of lipids in the mechanisms of membrane proteins, including allostery [ 34 ], we measured the substrate saturation profile for DDM-solubilized Dh-mPPase and compared it with the profile for the IMV-bound enzyme (the uppermost curves in Figure 3 and Figure 5 ). This comparison demonstrated the close similarity of the two profiles ( Figure S3 ) and the parameters derived therefrom ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Experimental studies have also been carried out that provide evidence of the activation of transmembrane proteins as a result of alterations to the lipid composition, e.g., using the mild detergent Triton X-100 [541,542], the relationship between lateral pressure profile and lipid composition was investigated both experimentally [697] and through MD simulation [698]. A few MD simulation studies found specific effects due to direct lipid interaction on protein behavior e.g., [699][700][701][702][703][704][705]; in most cases, the cholesterol molecules in the membrane were, however, most frequently shown to play the role of modulating the behavior of membrane proteins [706][707][708][709][710].…”
Section: Drug Membrane Interaction Can Play a Role In The Mechanism Of Drug Action-case Of Anestheticsmentioning
confidence: 99%
“…Since different chemical environments will result in different 13 C chemical shift, the observed broad peak ranging from 165 to 178 ppm indicated the multiple chemical environments which the Vpr Cys-76 residue experiences. Lipid membranes have been shown to play active roles in modulating the functions of membrane associated proteins or membrane proteins [ 48 , 49 , 50 , 51 , 52 ]. Thus, the membrane cannot be viewed as a passive supporting component for the membrane protein due to the couplings between protein and membrane.…”
Section: Resultsmentioning
confidence: 99%